Tree species richness and water availability interact to affect soil microbial processes. (April 2021) - Strukelj, Manuella; Parker, William; Corcket, Emmanuel; Augusto, Laurent; Khlifa, Rim; Jactel, Hervé; Munson, Alison D.
Abstract: The objective of this study was to examine the interactive influence of tree diversity and water availability on microbial functioning in surface soil (0–10 cm). The study was conducted at two field experiments (ages 4.2 and 9.0 years, respectively) of the TreeDivNet platform that established plantations with a gradient of tree species richness exposed to high and low water availability treatments. Soil microbial biomass, activity, functional diversity and functional identity were estimated using the MicroResp™ method. Soil organic carbon and several other variables potentially associated with soil processes (soil moisture, soil and air temperature, soil pH, soil C:N ratio, tree biomass) were also measured. Our results indicate that tree species richness significantly increased soil microbial biomass and, to a lesser extent, soil microbial activity in the high water availability treatment, at both trial sites. However, tree species richness effects on microbial processes were not expressed in the low water availability treatment, contrary to the stress-gradient hypothesis. Tree species richness and water treatment interaction impacted microbial biomass and activity through their effects on microbial functional diversity and identity at one site and air temperature at the other site. In conclusion, the mechanisms through which tree diversity creates bottom-up effects on biological soil processes depend on environmental conditions and time following the establishment of tree communities. Future research relating diversity and water availability effects on soil microbial processes should consider functional traits of tree species and a larger range of trophic levels including herbivores and soil fauna to better understand biodiversity-soil ecosystem function relationships in forest ecosystems. Highlights: Soil was sampled in 2 tree diversity experiments that also manipulated water supply. Microbial biomass increased with diversity, but only under high water availability. Soil organic carbon was not affected by tree diversity nor by water availability. Tree diversity impacted soil through microbial functional diversity and temperature. Future research should consider functional traits of trees and larger food web.